The meaning of the correct use of the terms, concerning the drilling of geological-exploration holes - L. D. Bazanov (Известия высших учебных заведений: Геология и разведка, 2015)
The paper discusses the problem of the use of main terms and definition of notions, used in the branch of technology and technics of holes drilling during exploration of mineral deposits. The analysis of terms use in relation of drilling holes while exploring all types of mineral sources is presented. The terminology, regarding drilling of wells of different direction, is considered. The proposed classification of terms consists of three groups.